2022
DOI: 10.1038/s41525-021-00273-x
|View full text |Cite
|
Sign up to set email alerts
|

Expanding the mutation and phenotype spectrum of MYH3-associated skeletal disorders

Abstract: Pathogenic variants in MYH3 cause distal arthrogryposis type 2A and type 2B3 as well as contractures, pterygia and spondylocarpotarsal fusion syndromes types 1A and 1B. These disorders are ultra-rare and their natural course and phenotypic variability are not well described. In this study, we summarize the clinical features and genetic findings of 17 patients from 10 unrelated families with vertebral malformations caused by dominant or recessive pathogenic variants in MYH3. Twelve novel pathogenic variants in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 29 publications
(40 reference statements)
0
11
0
2
Order By: Relevance
“…Epha5 (R6) is involved in axon guidance, whereas Slc1a3 (R8) is involved in regulation of excitatory neurotransmission in the CNS 18 . Myh3 (R3) is associated with muscle contraction 24 . Col2a1 (R7), which shows specific expression in cartilaginous tissues, has an essential role in normal embryonic skeleton development 18 .…”
Section: Spatial Comapping Of Mouse Embryomentioning
confidence: 99%
“…Epha5 (R6) is involved in axon guidance, whereas Slc1a3 (R8) is involved in regulation of excitatory neurotransmission in the CNS 18 . Myh3 (R3) is associated with muscle contraction 24 . Col2a1 (R7), which shows specific expression in cartilaginous tissues, has an essential role in normal embryonic skeleton development 18 .…”
Section: Spatial Comapping Of Mouse Embryomentioning
confidence: 99%
“…2 The variants leading to CPSFS1A and CPSFS1B are found to be located in any of the domains. 4 In the present study, the c.1024T>G (p.Phe342Val) variant of Fetus 1 is located within the head domain, and the c.3872A>C (p.Gln1291Pro) variant of Fetus 2 is located in the coiled-coil tail domain. Therefore, their phenotypes varied greatly.…”
Section: Gestation At Diagnosismentioning
confidence: 45%
“…The MYH3 variant is associated with distal arthrogryposis type 2A (Freeman‐Sheldon syndrome), distal arthrogryposis type 2B3 (Sheldon‐Hall syndrome), CPSFS1A (Contractures, pterygia, and spondylocarpostarsal fusion syndrome 1A) and CPSFS1B 2,3 . The diagnosis of MYH3 ‐associated disorders mainly depends on the clinical characteristics 4 . Sheldon‐Hall syndrome is the most common distal arthrogryposis, and Freeman‐Sheldon syndrome is one of the most severe distal arthrogryposes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is highly expressed during embryonic and fetal development, and is an important part of myo lament in skeletal muscle cell and non muscle cell 48 . Past researches has focused on the correlation between Myh3 with muscle-related disorders, but the role of Myh3 in FS has not been reported in studies 49 . This study found that Tuina can inhibit the capsule brosis through promoting Myh3 phosphorylation at S1916, S1148, S949 and T379, which indicated that Myh3 phosphorylation plays an important role in the mechanism of the treatment of Tuina therapy in FS.…”
Section: Discussionmentioning
confidence: 99%